PROTOTYPE SISTEM MONITORING KESEHATAN TUBUH MENGGUNAKAN IOT BERBASIS ANDROID - Abdul Razaq Fatta Utama; Sunarsan Sitohang (Computer Science and Industrial Engineering, 2025)
IoT (Internet of Things) is a concept that utilizes the internet network to connect various devices into a machine and allows these devices to operate automatically by collecting data in real time. body accurately and quickly. The heart works as a blood pumping device and is a very fatal organ if it does not work properly. This condition is a heart disorder which involves a delay in blood supply to the heart muscles because the blood vessels are blocked and the heart becomes abnormal. Heart problems or abnormal functioning of the heart can result in a 50% death rate. However, some people have difficulty reaching hospitals because they live in rural areas. Thus, it is hoped that today's advanced technology can help make the work of nurses easier and can help the medical field work in diagnosing patients quickly and precisely, and can be reached by all people, such as health monitoring tools based on body temperature. This tool can diagnose normal or abnormal heart conditions based on detection sensors connected to the device using network media and uses Android as a platform that provides an intuitive interface so that it can be adjusted to the needs or desires of a client or researcher. In this way, a Prototype tool is created, which is an initial design model for a design before increasing product sales.